Philogenia nemesioi, a new damselfly from Peru (Odonata, Megapodagrionidae) - Angelo B. M. Machado (Revista Brasileira de Entomologia, 2013)
Philogenia nemesioi, a new damselfly from Peru (Odonata, Megapodagrionidae). Philogenia nemesioi sp. nov. is described and illustrated based on one male specimen collected on forests of the eastern slope of the Peruvian Andes at 900 m. It belongs to the cristalina group, but differs from other species of the group by the structure of the anal appendage.